Thousands of years of Malay and Chinese population history in Indonesia and its implication on Paternity Index in DNA paternity testing. Issue 2 (March 2023) - Syukriani, Yoni; Wulandari, Ari Sri; Wanranto, Busyra; Hidayat, Yuyun
Highlights: Genetic assimilation might affect cLR in paternity testing. cLR and genetic similarity analysis are valuable in choosing allele frequency panels. Combined Fst MDS is an alternative perspective in choosing allele frequency panels. Abstract: The existence of the Chinese population in the predominantly Malay population in Indonesia can be traced back thousands of years, and it has been suspected that it played an essential role in the history of the Malay population origin in Maritime South East Asia. With the fact that the Malay-Indonesian population is currently predominant compared to the Chinese population in Indonesia (Chinese-Indonesian), the selection of the origin of the STRs allele frequency panel population becomes an issue in DNA profiling, including in paternity testing. This study analyses the genetic relationship between the Chinese-Indonesian and Malay-Indonesian populations and how this affects the Paternity Index (PI) ​​calculation in paternity test cases. The study of the relationship between populations was carried out using neighbour-joining (NJ) tree analysis and multidimensional scaling (MDS) on the allele frequency panel of 19 autosomal STRs loci of Malay-Indonesian (n = 210) and Chinese-Indonesian (n = 78) populations. Four population groups were used as references: Malay-Malaysian, Filipino, Chinese, and Caucasian. An MDS analysis was also performed based on the pairwise FST calculation. The combined Paternity Index (CPI) calculation was carried out on 132 paternity cases from the Malay-Indonesian population with inclusive results using a panel of allele frequencies from the six populations. The pairwise FST MDS indicates a closer relationship between the Chinese-Indonesian and Malay-Indonesian compared to the Chinese population, which is in line with the CPIs comparison test. The outcome suggests that the alternative use of allele frequency database between Malay-Indonesian and Chinese-Indonesian for CPI calculations is not very influential. These results can also be considered in studying the extent of genetic assimilation between the two populations. In addition, these results support the robustness claim of multivariate analysis to represent phenomena that phylogenetic analyses may not be able to demonstrate, especially for massive panel data.